SISTEM PENGOLAHAN DATA WARGA BERBASIS WEB MENGGUNAKAN METODE SPATIAL CLUSTERING K-MEANS PADA DESA GROGOL SEBRANG - Wahyudi; Tri Hidayati (CV. Multi Kreasi Media, 2023)
The development of the world of technology makes computer systems grow. These developments have broad implications for all sectors, including government agencies. The government agency is located in Grogol Sebrang Village. Collection of precise, fast and accurate population data is needed to anticipate an increase in the population of a village. The main objective of this research is to design a Population Data Collection System and a web-based letter printing service, thereby helping speed and quality in delivering information and facilitating the service of printing correspondence to be more effective and efficient. The method used in developing this system is SDLC (System Development Life Cycle) with the waterfall process model. In this study, besides explaining the theoretical studies used as the basis for the preparation, system design and web creation will also be discussed. So that it is hoped that it can be implemented in a product that will fix all the deficiencies that exist in the old system. The method taken by the author is to carry out observations, interviews, literary studies, analysis and design of information systems. Where the existence of a computerized Population Data Collection System is expected to process data faster and easier than manually / bookkeeping. This information system was built using Code Igniter using PHP language. Data flow and system design use Object Oriented Programming (OOP), while table design in the database uses Entity Relationship Diagram (ERD).